Tailoring van der Waals dispersion interactions with external electric charges - Andrii Kleshchonok (Nature Portfolio, 2018)
The description of van der Waals interactions should often account for coupling with pervasive electric fields, but this effect has been omitted in atomistic simulations. Here, the authors develop a model to study the effects of external charge on long-range van der Waals interactions.